The profile of studies on renewable energy in sustainable supply chain - Marques, Eduardo do Carmo (2020)
Over the years, has been growing policies aiming toreducethe green-houses gases emissions–GHG, which lead for the searching ofsustainable alter-native solutions. One waymitigatesthe GHG emissionsisthe use of renewable energy sources. Nevertheless, for the use of such resources there are a series of processes inherent to the energy production and consumption, being the supply chain one of the principals. Based on this, the main objective of present article is tomapthe roleof renewable energies inside the context of sustainable supply chain, observing how the studies have been developed, looking for the main re-searchers, organizations andcollaboration networks, being at final a mapping of the 15 most cited studies in area. The research was carried out with the papers published atWeb of Science database, using VantagePoint software to quantify the information’s, including the evolution of studies over time until 2019.It was possible to perceivethat the researchhasbeen growingsince 2010, moreover, subjects related to biomass, biofuels and photovoltaic energy were the most re-currentat the most cited. However, within this framework, the theme presented itself as new and that there are still great potentials to be explored